Tahap-Tahap Pendidikan Karakter Dalam Pemikiran Ki Ageng Suryomentaram dan Relevansinya dengan Pendidikan Akhlak Islam - Sumedi (Jurnal Pendidikan Islam, 2012)
Morality shows people’s life quality and how moral education could influence them. Religious people have an assumption that religion always teaches followers to do good and forbid them from doing badness. Islam, in the context of Indonesia, is of course influenced by the real condition of the society. In relation to this, there is Javanese philosopher, Ki Ageng Suryomemtaram, who thought the character building that is still relevant. He thought, “feeling is the center of everyone’s personality”. Based on his idea and feeling, he divides them into four dimensions of life.